Prizes for the 1986 y-Walk participants - Brock, Trish (photographer):::Creator::::::::::::
Negative shows Jenifer Williams, who appears to be African American, holding paper in her hands and standing at a microphone outdoors. She is probably announcing prize winners. A tall man with a moustache is standing close to Jenifer and is holding something in his hands that may be a prize. He is making a face. There is a table with plants and a trophy on it behind Jenifer. Other people are watching, some with balloons and some wearing tee shirts that read: "Walk for women. YWCA 1986."